Milk Producers’ Awareness of Milk-Borne Zoonoses In Baghabarighat Milk Shed Areas of Bangladesh - Shanta, Solama A; Aktaruzzaman, Muhammad; Ahmed, Md Siam; Hasan, Md Razibul; Islam, M Ariful (Research in Agriculture Livestock and Fisheries, 2023)
The present study was undertaken to assess the farmers’ knowledge and awareness of milkborne zoonoses in Bhaghabarighat Milk Shed Areas of Bangladesh. A cross-sectional study was carried out in randomly selected 270 dairy farmers in Pabna and Sirajgonj district. A pretested structured questionnaire was used to collect information from respondents regarding different aspects of milk-borne zoonosis. Data were collected from farmers, with inclusion criteria of having at least 2 cows with farming experience of more than 6 months. The study showed that almost 80% of the farmers were unable to name any milk-borne zoonotic disease, whereas rest of the farmers had a little bit knowledge about milk-borne zoonoses those were relatively educated and experienced farmers. About 23% of the farmers had no knowledge of the fact that raw milk can be a potential source of disease transmission. The majority of the respondents (99%) did not receive any formal training about zoonotic diseases. Among the respondents’ awareness levels of milkborne zoonoses were 4.5%, 9.2%, 17.4%, 54.84% and 82.1% for brucellosis, anthrax, tuberculosis, mastitis and diarrhea, respectively. The behavioral practices of dairy farmers observed to increase the risk of milk-borne zoonoses transmission were: consumption of raw milk (13%), lack of cooling system (100%), no milk routine testing, and none farmers’ did medical check-up. 87% of the respondents preferred to use boiled milk. The farmers’ overall knowledge about milk-borne zoonoses was inadequate. In conclusion, awareness and training programs about milking hygiene and handling can improve disease control and reduce the public health risk of milk-borne zoonoses. Vol. 9, No. 3, December 2022: 307-312